2020
DOI: 10.2308/jeta-2020-020
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the Robots: A Proposed Course in Robotic Process Automation

Abstract: Robotic Process Automation (RPA) is poised to change the accounting and auditing workplace significantly.  RPA will likely shift the skillset needed by all accountants. Therefore, the accounting curriculum quickly needs to adapt to educate accountants of the future in this skillset. This paper presents a proposed course, focusing on the automation of accounting processes, to add to the accounting curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…This paper contributes to accounting automation literature as follows. First, previous studies discuss automation and digitalization in general from different perspectives, such as companies (Kokina and Blanchette, 2019, Cooper et al, 2020, Lacurezeanu et al, 2020, professional regulation (Troshani et al, 2018), accounting education (Vincent et al, 2020;Novak et al, 2021), while the present study discusses it from the accounting practitioners' perspective. Second, this paper uses an experimental method, whilst previous studies in accounting automation field use methods as interviews Kokina and Blanchette (2019) or case studies (Fernandez and Aman, 2018;Gotthardt et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…This paper contributes to accounting automation literature as follows. First, previous studies discuss automation and digitalization in general from different perspectives, such as companies (Kokina and Blanchette, 2019, Cooper et al, 2020, Lacurezeanu et al, 2020, professional regulation (Troshani et al, 2018), accounting education (Vincent et al, 2020;Novak et al, 2021), while the present study discusses it from the accounting practitioners' perspective. Second, this paper uses an experimental method, whilst previous studies in accounting automation field use methods as interviews Kokina and Blanchette (2019) or case studies (Fernandez and Aman, 2018;Gotthardt et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Another important issue concerns practically preparing personnel for the introduction of robotic assistance. According to Kruskopf et al (2019), RPA and the associated new technologies influence future jobs and the skills required for such jobs; Vincent et al (2020) echo that RPA is likely to become a necessary skill required by the job market for accountants. New professional opportunities are open for accounting professionals such as blockchain accountants, analytics gurus, historical accounting analysts, cloud accounting specialists, systems integrators, cybercrime accountants, strategic accounting analysts, robot coordinators, and data security accountants.…”
Section: Resultsmentioning
confidence: 99%
“…The exercises by which students could be taught relevant skills could include various RPA applications such as connecting to an ERP system, extracting Internet data, and entering Excel spreadsheet data in PDF files (Keys and Zhang 2020). Vincent et al (2020) propose including a course based on automated accounting processes in the accounting syllabus. The course would contain an overview of RPA, explore how to use RPA tools, and concentrate on an advancement framework for technology implementation and application governance (Vincent et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, we are among the first to conduct an extensive review of the growing academic literature on digital transformation in the external audit arena. Prior research offers conceptual frameworks (e.g., Appelbaum et al, 2021; Dai & Vasarhelyi, 2017) and thought pieces related to education (e.g., Vincent, Igou, et al, 2020; Vincent, Skjellum, et al, 2020). Notably, relatively few studies we identified were published in top tier (e.g., Financial Times 50 journals) or general interest journals.…”
Section: Introductionmentioning
confidence: 99%